Effects of Ultraviolet-C (UV-C) radiation on germination, seedling growth, and abiotic stress response in waxy corn (Zea mays L.) - Garbeles, Darwin; Milan, Marygrace; Palmiano, Dariel (Academia Journal of Biology, 2024)
Waxy corn (Zea mays L.) is an important crop in the Philippines, but its production has been hampered by various abiotic stresses, including waterlogging and salinity. This study investigates the potential of using UV-C radiation as a strategy to improve the growth performance of waxy corn under these stressful conditions. The study utilized a completely randomized design to evaluate the effects of different durations of 254 nm UV-C radiation (0, 30, 60, 90, & 120 min) on the germination and early seedling growth of waxy corn. Germination parameters and seedling growth under normal, waterlogged, and saline conditions were evaluated. The results showed that moderate UV-C exposure (30–60 minutes) had a beneficial effect on waxy corn seed germination, with significantly higher germination percentages and faster times to reach 50% germination compared to the control. However, longer exposure times (90–120 minutes) had a detrimental impact on germination. For seedling growth, moderate UV-C exposure (30–60 minutes) generally had a stimulatory effect, increasing various growth parameters under normal and waterlogged conditions. Longer exposure times (90–120 minutes) resulted in values closer to or not significantly different from the control. Under saline stress, increasing UV-C exposure time had a generally positive effect on seedling growth, with the optimal duration being around 90 minutes. The findings of this study suggest that the optimal duration of UV-C exposure for enhancing waxy corn germination and seedling growth varies depending on the specific environmental conditions. Moderate UV-C exposure (30–60 minutes) can be beneficial for improving seed germination and early seedling growth under normal and waterlogged conditions, while longer exposure times (> 90 minutes) are more suitable for enhancing growth under saline stress.